Development of Handball Athletes' Potential: Coaches' Strategies in Training Beginner Handball Athletes - Muhammad Fadli (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aims to examine coaches’ strategies in developing the potential of beginner handball athletes comprehensively, covering technical, tactical, physical, and psychological aspects. Early-age athlete development is an essential foundation in building a competitive handball sports ecosystem at both national and international levels. The research employed a descriptive qualitative method with a case study approach conducted at beginner handball clubs in South Sulawesi Province. Data were collected through participatory observation, in-depth interviews with certified coaches and athletes, and analysis of training program documents. The findings indicate that effective coaching strategies include the design of structured and progressive training programs, the application of individualized approaches based on athletes’ ability profiles, the development of character and competitive mentality, and the implementation of regular performance monitoring. Athlete-centered coaching has been proven to significantly enhance the intrinsic motivation and technical abilities of beginner athletes. The conclusion of this study emphasizes that the success of beginner handball athlete development is highly determined by the quality of coaching strategies that are adaptive, communicative, and grounded in scientific evidence